The singing athlete : brain-based training for your voice - Byrne, Andrew (Andrew Byrne Studio Inc., 2020)
Singing is a sport. And the athletic skills that are required to be a great vocalist come from one source: your brain. The Singing Athlete is the first book of its kind: a view on voice training through the lens of both the physical body and the nervous system. As one of the top teachers of professional Broadway performers, Andrew Byrne has developed a unique synthesis of athletics and neuroscience that will guide you to higher levels of performance. Through the book and the accompanying videos, you will learn to: breathe correctly for stress reduction and optimal vocal support; exercise your tongue, jaw, and throat in ways that lower threat in your brain; use your ears and eyes to improve vocal range and stamina; heal any scars that might be holding you back, eliminate reflux, tinnitus, sinus problems, and other vocal stumbling blocks, move better, feel better, and sing better. Whether you're a beginner or a seasoned professional, The Singing Athlete will allow you to harness the power of the nervous system to make yourself the singer you've always wanted to be [Publisher description]